THE EVALUATION OF SINGLET OXYGEN QUENCHING AND SUNSCREEN ACTIVITY OF CORN COB EXTRACT - Suryanto, Edi; Momuat, Lidya Irma; Yudistira, Adithya; Wehantouw, Frenly (Indonesian Journal of Pharmacy, 2013)
The corn cob waste has been reported to have antioxidant activity. Active compound such as antioxidant has been considered as potential sunscreen resources. The objectives of this research were to determine singlet oxygen quenching and sunscreen activity of corn cob. Corn cob was extracted using ethanol 20, 40, 60 and 80% by reflux for 2h at 78oC. The singlet oxygen quenching activity was evaluated by photooxidation of linoleic acid. Singlet oxygen quenching activity was conducted using linoleic acid as substrate containing erythrosine as a sensitizer and exposed under continuous illumination (4000 lux) with the fluorescent light for up to 5h. The sunscreen activity was evaluated by sun protection factor (SPF) using spectrophotometry UV-Vis. Ethanol extract 80% (E80) shows the highest total phenolic content followed with E60, E40 and E20. The result shows that the lowest singlet oxygen quenching activity was E20 (15.63%), and the highest was E80 by 65.63% percentage of inhibition. SPF value of E20, E40, E60, and E80 at concentration 200μg/mL were 7.52; 12.24; 15.81 and 17.78, respectively. SPF value increase with the increasing of concentration, total phenolic content and singlet oxygen quenching activity. The conclusion of this research was corn cob extract possess phytochemical compound having potency as singlet oxygen quencher and sunscreen active compound.Keywords: corn cob, phenolic phytochemical, singlet oxygen quenching, sunscreens